Mammalian Oocyte Regulation Methods and Protocols - Homer, Hayden A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Mammalian oocytes occupy a critical nexus in reproduction as they not only contribute half the genetic makeup of the embryo but also provide virtually all of the cytoplasmic building blocks required for sustaining embryogenesis. The journey that transforms a primordial germ cell into a mature oocyte (or egg) capable of fertilisation and embryonic development is of unrivalled complexity. The end-product of this remarkable developmental process is the “mature” egg, now replete with macromolecules and organelles, and poised to support embryonic development if fertilisation should occur. Given the importance of the oocyte for embryonic development, it is of no surprise that the oocyte holds centre stage in fertility clinics and greatly influences the outcome of assisted reproductive treatments (ARTs). Mammalian Oocyte Regulation: Methods and Protocols provides a highly diverse compendium of detailed methodologies - primarily focusing on the murine model but also including chapters on human oocytes - for enabling researchers to interrogate every aspect of mammalian oocyte development including recombination, meiotic maturation, oocyte substrate uptake, chromosomal segregation and fertilisation. Written in the highly successful Methods in Molecular Biology™ series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, Mammalian Oocyte Regulation: Methods and Protocols serves as an ideal guide to novice oocyte researchers, experts who wish to add another dimension to their established portfolio, as well as the wider research community.
Studying Recombination in Mouse Oocytes -- Analysis of Recombinants in Female Mouse Meiosis -- Studying Meiosis Specific Cohesins in Mouse Embryonic Oocytes -- Immunohistochemical Approaches to the Study of Human Fetal Ovarian Development -- Protein Kinase Assays for Measuring MPF and MAPK Activities in Mouse and Rat Oocytes and Early Embryos -- Time-Lapse Epi-Fluorescence Imaging of Expressed cRNA to Cyclin B1 for Studying Meiosis I in Mouse Oocytes -- Using FRET to Study RanGTP Gradients in Live Mouse Oocytes -- Making cRNA for Microinjection and Expression of Fluorescently-Tagged Proteins for Live-Cell Imaging in Oocytes -- RNAi-Based Methods for Gene Silencing in Mouse Oocytes -- Micro-Injection of Morpholino Oligonucleotides for Depleting Securin in Mouse Oocytes -- Measuring Transport and Accumulation of Radiolabelled Substrates in Oocytes and Embryos -- Immunofluorescence Staining of Spindles, Chromosomes and Kinetochores in Human Oocytes -- Studying the Roles of Aurora-C Kinase During Meiosis in Mouse Oocytes -- Chromosome Spreads with Centromere Staining in Mouse Oocytes -- Preparation of Mammalian Oocytes for Transmission Electron Microscopy -- Measuring Ca2+ Oscillations in Mammalian Eggs -- Counting Chromosomes in Intact Eggs -- Free-Hand Bisection of Mouse Oocytes and Embryos -- Microarray-CGH for the Assessment of Aneuploidy in Human Polar Bodies and Oocytes -- Nuclear Transfer in the Mouse Oocyte.
Keywords: Cell biology; Embryology; Cell Biology; Embryology